Clonal expansion of Tn1546-like transposon-carrying vancomycin-resistant Enterococcus faecium, a nationwide study in Taiwan, 2004-2018 - Ying-Chi Huang; Feng-Jui Chen; I-Wen Huang; Han-Chieh Wu; Shu-Chen Kuo; Tzu-Wen Huang; Tsai-Ling Lauderdale (Journal of Global Antimicrobial Resistance)
Objectives: The prevalence of vancomycin-resistant Enterococcus faecium (VREfm) has increased significantly in Taiwan. We investigated the molecular epidemiology of clinical VREfm isolates to increase our understanding on their spread and changes in population structure over a 14-year span. Methods: A total of 1113 E. faecium isolates were collected biennially from 2004 to 2018 in Taiwan. MICs were determined by broth microdilution. Whole-genome sequencing (WGS) was performed on 229 VREfm isolates to characterize their genetic environment of vancomycin resistance and wgMLST was used to investigate their clonal relationship. Results: Among the 229 isolates, ST17 and ST78 predominated, especially during the later years, and their prevalences increased from 14.6% (7/48) and 25.0% (12/48) in 2004–2010 to 47.5% (87/181) and 29.8% (54/181) in 2012–2018, respectively. Four types of vanA-carrying Tn1546 variants were detected, with type 1 and type 2 predominated. Type 1 Tn1546 contained an addition of IS1251, while type 2 resembled type 1 but had an addition of IS1678. wgMLST revealed several distinct clusters of ST17 and ST78 isolates, with type 1 Tn1546-harbouring ST17-Cluster 16 being the largest and most widespread clones throughout the study years. Type 2 Tn1546-carrying ST78 became a predominant clone (Cluster 21) after 2012. Isolates within these clusters are highly similar despite being from different hospitals, regions, and study year. Conclusion: The increase of VREfm in Taiwan was attributed to horizontal transfer of vanA-carrying Tn1546 variants between different STs and spread of persistent clones. This study highlights the importance of integrating WGS into surveillance to combat antimicrobial resistance.